2000
DOI: 10.1259/bjr.73.873.11064656
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of dose in panoramic dental radiology.

Abstract: The National Radiological Protection Board (NRPB) has recommended the introduction of dose-width product (DWP) for the measurement of patient dose in panoramic dental radiology and has proposed a reference level of 65 mGy mm for adult exposures. This paper describes a method for measuring DWP and dose-area product (DAP) using thermoluminescent dosemeters (TLDs). The technique was used on 16 sets with a range of exposure settings. The mean value of DWP was 14% higher than the mean value reported from a survey b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 2 publications
2
14
0
3
Order By: Relevance
“…Dental radiology is being extensively used especially after the consolidation of the dental implant technique (2).Therefore radiographic findings play an important role. Entrance surface dose(ESD) ,(named skin absorbed dose in current article), and dose-area product (DAP) are the most important parameters measured in diagnostic Radiology (3).Due to increasing radiological examinations, patient protection against X-rays is important. Therefore, all national and international forums have specific recommendations to further protection of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dental radiology is being extensively used especially after the consolidation of the dental implant technique (2).Therefore radiographic findings play an important role. Entrance surface dose(ESD) ,(named skin absorbed dose in current article), and dose-area product (DAP) are the most important parameters measured in diagnostic Radiology (3).Due to increasing radiological examinations, patient protection against X-rays is important. Therefore, all national and international forums have specific recommendations to further protection of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Au niveau de la comparaison du risque radiologique, la situation est plus complexe puisque l'irradiation de la thyroïde varie sensiblement d'une installation ou d'un positionnement à l'autre. Pour tenir compte des différentes situations d'irradiation, un facteur de conversion moyen de 0,06 mSv Gy -1 cm -2 est proposé dans la littérature (Williams et Montgomery, 2000). Un examen sur un OPG récent délivre ainsi une dose efficace d'environ 5 µSv au patient.…”
Section: Discussionunclassified
“…Un facteur de conversion moyen de 0,03 mSv Gy -1 cm -2 est utilisé dans cette étude. (Williams et Montgomery, 2000). En outre, des mesures par TLD ont été effectuées sur l'OPG analogique le plus récent pour évaluer la répartition de la dose à la peau.…”
Section: Tableau IIunclassified
“…In the case of the cervical spine and the thyroid gland on the left side (the dose measured in the phantom), the right and left lens of the eye, as well as at the height of the right and left eye lenses (the surface of the phantom), there was no measured statistical difference in absorbed dose values (p > 0.05). Most papers concerning radiation dose estimation in panoramic radiography draw comparisons between conventional and digital panoramic radiography [11,[18][19][20]. These studies have concluded that any dose reduction results in an image quality difference with a predominance of the conventional panoramic device [21].…”
Section: Eye Lens Exposure During Extraoral Dental Diagnosticsmentioning
confidence: 99%